Identification of Apolipoprotein E4 inhibitors for Alzheimer's Disease Therapy through a Large-Scale Virtual Screening. Issue 23 (2022) - Krass, Emily; Zhai, Tianhua; Huang, Zuyi
Abstract: Alzheimer's disease (AD), a neurodegenerative disorder, is characterized by its ability to cause memory loss and damage other cognitive functions. Aggregation of beta amyloid plaques (Aβ) and neurofibrillary tangles in brain are responsible for the development of Alzheimer's disease (AD). Apolipoprotein E4 allele (ApoE) is a high-risk genetic factor for AD compared to other alleles. The ApoE4 protein has been shown to increase Aβ accumulation by directly binding to Aβ as well as interfering with Aβ clearance that is associated with other receptors. Currently, many attempts targeting Aβ and tau proteins have been proven mostly unsuccessful. In this study, Apolipoprotein E4 (ApoE4) was chosen as the protein target based on its role in the main pathological hallmarks of AD. A computational approach was then developed to identify small-molecule inhibitors of ApoE4 protein to provide potential therapeutical options for Alzheimer's disease. In particular, ligand-protein docking and chemical clustering were conducted to virtually screen 1.5 million large compounds and select inhibitors with diverse common substructures. In conclusion, total 577 potential ApoE4 inhibitors were newly identified, which would provide drug candidates for further experiment assays.